EFFECTS OF HEATING ON DEFORMATION OF VESICLE MODEL OF RED BLOOD CELL BY USING LANGEVIN DYNAMICS - Dewi Lestari, Mutiara
Red blood cell is essential for human life. It supplies oxygen to whole human body. The membrane of red blood cell is highly exible membrane. Vesicle is a membrane-bounded bubbles model system. It is usually used to study about dynamic behavior of membranes. We investigate dynamics of vesicle deformation into red blood cells membrane. We assume the particles of red blood cell membrane act similarly to Brownian particle motion in surrounding medium. Therefore, we use Langevin dynamics to describe particles motion. We investigate the eect of heating human blood above normal body tempa- rature, where hemolysis of the red blood cell will occur. Based on our result, hemolysis occurs at 50C.